A photoresist resin material prepared by halogenation modification and preparation method thereof

Modified polymers by halogenated reactions, the glass transition temperature and exposure sensitivity of the photoresist resin are improved, and the problems of low sensitivity, low resolution and poor pattern stability of the existing photoresist resin are solved, achieving efficient and stable photoresist performance.

CN115991815BActive Publication Date: 2025-03-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211638993.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-03-07
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

The existing photoresist resins have problems such as low sensitivity, low resolution, long exposure time, and poor pattern stability after development.

Method used

The polymer is modified by halogenation reaction, and the glass transition temperature and exposure sensitivity of the photoresist resin are improved, and a photoresist resin material with excellent exposure performance is prepared.

Benefits of technology

The exposure sensitivity and resolution of photoresist is improved, the exposure time is shortened, and the graphics stability after development is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115991815B_ABST
    Figure CN115991815B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photoresists, and discloses a halogenated modified photoresist resin material and a preparation method thereof. The present invention utilizes a halogenation method to modify a polymer, and prepares a photoresist resin material having excellent exposure performance, adjustable halogenated functionality, and capable of achieving a resin glass transition temperature, photoresist exposure sensitivity, and adjustable aspect ratio. The present invention also provides a preparation method for the photoresist resin material, which is of great significance for developing a photoresist resin material having high sensitivity, high resolution, short exposure time, and high pattern stability after development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to a photoresist resin material prepared by halogenation modification and a preparation method thereof. Background Art

[0002] Photolithography refers to the process technology of transferring the pattern on the mask to the substrate using photoresist by combining the principle of optical-chemical reaction with etching method in integrated circuits. It is the core technology of emerging industries such as 5G, IT and artificial intelligence. The development of photolithography mainly relies on the continuous reduction of the wavelength of the light source. From g-line (436nm), i-line (365nm), KrF (248nm), ArF (193nm) to today's extreme ultraviolet (EUV, 13.5nm), the process technology of integrated circuits is constantly improving, and photoresists are also constantly updated. Photoresists are composed of film-forming resins, photosensitizers, solvents and additives. Photoresists can be divided into positive and negative photoresists according to the solubility changes before and after the irradiation of the photoresist material. In the developer, the exposed area softens and dissolves, and the unexposed area remains on the substrate, which is a positive photoresist, and vice versa, it is a negative photoresist.

[0003] There are many types of photoresists. It is a comprehensive field that integrates many disciplines such as photochemistry, organic synthesis, polymer synthesis, and electronic information. It is a typical technology-intensive industry. At present, the electron beam photoresists commonly used in the large-scale integrated circuit industry are mainly polymethyl methacrylate (PMMA) series. Positive electron beam photoresists are one of the classic general materials used in electron beam patterning processes. They have high resolution, but low sensitivity and require long exposure time. Modified electron beam photoresists, such as ZEP series photoresists, which are alternating copolymers prepared using α-methyl chloroacrylate and α-methylstyrene, have a sensitivity one order of magnitude higher than that of the PMMA series, and a resolution comparable to that of the PMMA series, but the stability of the graphics after development is slightly worse. Therefore, the development of photoresists with high sensitivity, high resolution, short exposure time, and high stability of the graphics after development has become an urgent need in this field. Summary of the invention

[0004] In view of this, the present invention utilizes halogenation reaction to modify the polymer to synthesize the photoresist resin, thereby solving the problems of low sensitivity, low resolution, long exposure time and poor pattern stability after development existing in the existing photoresist resin.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The present invention provides a photoresist resin material prepared by halogen modification, and the structure of the photoresist resin material is:

[0007]

[0008] Wherein, u, v, w and z are the molar proportions of the structural unit, 0≤u<0.8, 0<v≤0.9, 0<w≤0.9, u+v+w=1;

[0009] R' is one or more of H, -CH3 and X;

[0010] X is one or more of -Cl, -Br, and -F;

[0011] R″ is one or more of H, -CH3 and Y, wherein Y is one or more of -Cl, -Br, -F;

[0012] Ar is one or more of a benzene ring and its derivatives, a naphthalene ring and its derivatives;

[0013] n is a positive integer greater than 0;

[0014] R1 is one or more of Formula I and Formula II;

[0015]

[0016] Wherein, R2 and R3 are independently -H, -CH3, -CH2CH3, C3~C 12 One or more of alkanes, benzene rings and their derivatives, naphthalene rings and their derivatives.

[0017] Preferably, u, v and w are the molar ratios of the structural units, 0≤u<0.2, 0<v≤0.7, 0<w≤0.8, u+v+w=1.

[0018] Preferably, the R′ is one or more of -CH3 and X; the X is one or more of -Cl and -Br; the R″ is one or more of H and Y, wherein Y is one or more of -Cl, -Br; the Ar is one or more of a benzene ring and a naphthalene ring.

[0019] Preferably, the benzene ring and its derivatives and the naphthalene ring and its derivatives are independently one or more of benzene, phenol, toluene, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, benzyl alcohol, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, dimethylnaphthalene, methylnaphthalene, trimethylnaphthalene and naphthalenemethanol.

[0020] The present invention also provides a method for preparing the halogenated modified photoresist resin material, comprising the following steps:

[0021] The polymer is dissolved in a solvent, and a halogenating agent is added to carry out a halogenating reaction. After the reaction is completed, the polymer is precipitated to obtain a photoresist resin material.

[0022] Preferably, the structure of the polymer is:

[0023]

[0024] Wherein, m and h are the molar ratios of the structural unit, 0<m≤0.9, 0<h≤0.9, m+h=1; RIII and RIV are independently one or more of H, -CH3;

[0025] Ar is one or more of a benzene ring and its derivatives, a naphthalene ring and its derivatives;

[0026] R1 is one or more of Formula I and Formula II;

[0027]

[0028] Wherein, R2 and R3 are independently -H, -CH3, -CH2CH3, C3~C 12 One of alkanes and their derivatives, benzene rings and their derivatives, naphthalene rings and their derivatives;

[0029] Preferably, the benzene ring and its derivatives and the naphthalene ring and its derivatives are independently one or more of benzene, phenol, toluene, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, benzyl alcohol, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, dimethylnaphthalene, methylnaphthalene, trimethylnaphthalene and naphthalenemethanol.

[0030] Preferably, Ar, R2 and R3 are independently one or more of -CH3, -CH2CH3, benzene ring and naphthalene ring.

[0031] Preferably, the polymer is one or more of a random copolymer, a block copolymer, and an alternating copolymer; at the same time, the random copolymer, the block copolymer, and the alternating copolymer can also be used as branches in branched (or hyperbranched) polymers, side chains in comb polymers, and branches in star polymers, etc.

[0032] Preferably, the solvent is one or more of carbon tetrachloride, 1,1,2,2-tetrachloroethane, anisole, propylene glycol monoalkyl ether, toluene, chlorobenzene, benzene, chloroform, dichloromethane, hexane, butyl acetate, neopentyl acetate, ethyl lactate, butyl lactate, amyl lactate, propylene glycol alkyl ether acetate, ethyl acetate, butyl acetate, cyclopentanone, cyclohexanone, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0033] Preferably, the halogenating agent is a mixture of N-chlorosuccinimide and benzoyl peroxide, a mixture of N-bromosuccinimide and benzoyl peroxide, a mixture of N-chlorosuccinimide and azobisisobutyronitrile, a mixture of N-bromosuccinimide and azobisisobutyronitrile, a mixture of N-chlorosuccinimide and sodium hydride, a mixture of N-bromosuccinimide and sodium hydride, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and azobisisobutyronitrile, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and benzoyl peroxide, a mixture of carbon tetrachloride and lithium diisopropylamide, ClF3, BrF3, One or more of PCl3, SO2Cl2, CF3OF, Br2, Cl2, F2, a mixture of HBr and dimethyl sulfoxide, a mixture of HCl and dimethyl sulfoxide, a mixture of HF and dimethyl sulfoxide, a mixture of NH4Br and potassium persulfate complex salt, a mixture of KBr and potassium persulfate complex salt, a mixture of KCl and potassium persulfate complex salt, a mixture of KBr and NaBO3·4H2O, N-chloroamine, S-chlorodimethylsulfonium chloride, S-chlorodimethylsulfonium bromide, a mixture of CuBr2 and tert-butyl nitrite, and a mixture of bromo-1,4-dioxane.

[0034] Preferably, the mass ratio of polymer:solvent:halogenating agent is 1:(1-100):(0.001-2).

[0035] Preferably, the reaction temperature of the halogenation reaction is -80 to 90° C., and the reaction time is 0.5 to 96 hours; the halogenated molar percentage of the photoresist resin material is 5-95%.

[0036] The present invention also provides the use of the halogenated modified photoresist resin material in photoresist. The photoresist comprises 1-15% of the halogenated modified photoresist resin material, 0.001-0.1% of an auxiliary agent and 84.9-98.999% of an organic solvent.

[0037] Preferably, the organic solvent is one or more of anisole, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, methyl isobutyl ketone, cyclopentanone, cyclohexanone, methyl ethyl ketone, diheptanone, ethyl lactate, ethyl acetate, butyl acetate, neopentyl acetate, xylene and toluene.

[0038] Preferably, the auxiliary agent includes one or more of a leveling agent, a defoamer, a sensitizer, a tackifier, a plasticizer, a dye, and a diluent.

[0039] The invention also provides application of the halogenated modified resin material in photoresist.

[0040] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0041] 1. The present invention can increase the glass transition temperature (T) of the polymer by halogenating the aromatic ring in the polymer. g ), thereby improving the aspect ratio of the photoresist exposure pattern;

[0042] 2. The present invention can improve the sensitivity of the obtained photoresist during exposure by halogenating the polymer main chain;

[0043] 3. The present invention utilizes a halogenation method to modify the polymer, and can prepare a resin material for photoresist with excellent exposure performance. The electron beam photoresist resin prepared in the present invention has the same exposure performance as the ZEP series electron beam photoresist, and has high pattern stability after development;

[0044] 4. The raw materials used in the present invention are widely available, the process is simple and easy to operate, and the halogenated functionality is adjustable, thereby achieving controllable regulation of the glass transition temperature of the polymer and the exposure sensitivity and aspect ratio of the photoresist. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0046] Figure 1 It is a comparison chart of the H-NMR spectra of the halogenated modified photoresist resin prepared in Example 4 and the unmodified resin.

[0047] Figure 2 It is a comparison chart of the H-NMR spectra of the halogenated modified photoresist resin prepared in Example 8 and the unmodified resin.

[0048] Figure 3 This is a SEM morphology image of the halogenated modified photoresist resin prepared in Example 9 after exposure.

[0049] Figure 4 It is a comparison chart of the H-NMR spectra of the halogenated modified photoresist resin prepared in Example 9 and the unmodified resin.

[0050] Figure 5 It is a comparison chart of the H-NMR spectra of the halogenated modified photoresist resin prepared in Example 21 and the unmodified resin. DETAILED DESCRIPTION

[0051] The present invention provides a photoresist resin material prepared by halogen modification, and the structure of the photoresist resin material is:

[0052]

[0053] In the present invention, u, v and w are the molar proportions of the structural unit; preferably, 0≤u<0.8, 0<v≤0.9, 0<w≤0.9, u+v+w=1; further preferably, 0≤u<0.5, 0<v≤0.8, 0<w≤0.7, u+v+w=1; more preferably, 0.2≤u<0.5, 0<v≤0.5, 0<w≤0.5, u+v+w=1.

[0054] In the present invention, R′ is preferably one or more of -H, -CH3, and X, more preferably H or -CH3, and more preferably -CH3; R″ is one or more of H, -CH3, and Y, more preferably H or Y, and more preferably Y.

[0055] In the present invention, X is preferably one or more of -Cl, -Br, and -F, more preferably -Cl or -Br, and more preferably -Cl; Y is preferably one or more of -Cl, -Br, and -F, more preferably -Cl or -Br, and more preferably -Cl.

[0056] In the present invention, Ar is preferably one or more of a benzene ring and its derivatives, a naphthalene ring and its derivatives, more preferably a benzene ring and a naphthalene ring, and more preferably a benzene ring.

[0057] In the present invention, n is preferably an integer greater than 0, more preferably an integer of 1 to 10, and even more preferably an integer of 1 to 2.

[0058] In the present invention, R1 is preferably one or more of Formula I and Formula II, and is further preferably Formula I;

[0059]

[0060] Among them, R2 and R3 are preferably independently -H, -CH3, -CH2CH3, C3~C 12 Alkanes, benzene rings and their derivatives, naphthalene rings and their derivatives, one or more, more preferably -CH3, -CH2CH3, C3-C 12 One or more of alkanes, more preferably one or more of -CH3, -CH2CH3.

[0061] In the present invention, the benzene ring and its derivatives and the naphthalene ring and its derivatives are independently preferably one or more of benzene, phenol, toluene, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, benzyl alcohol, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, dimethylnaphthalene, methylnaphthalene, trimethylnaphthalene, and naphthalenemethanol; more preferably one or more of phenol, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, methylnaphthalene, trimethylnaphthalene, and naphthalenemethanol;

[0062] The halogenated benzene is preferably one or more of bromobenzene, chlorobenzene, fluorobenzene, dichlorobenzene, trichlorobenzene, tetrachlorobenzene, pentachlorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, dibromobenzene, tribromobenzene, tetrabromobenzene and pentabromobenzene; more preferably one or more of chlorobenzene, fluorobenzene, pentachlorobenzene and pentafluorobenzene;

[0063] The halogenated naphthalene is preferably 1-chloronaphthalene, 1,2-dichloronaphthalene, 1,3-dichloronaphthalene, 1,4-dichloronaphthalene, 1,5-dichloronaphthalene, 1,6-dichloronaphthalene, 1,7-dichloronaphthalene, 1,8-dichloronaphthalene, 2,3-dichloronaphthalene, 2,4-dichloronaphthalene, 2,5-dichloronaphthalene, 2,6-dichloronaphthalene, 2,7-dichloronaphthalene, 1,4,5-trichloronaphthalene, 1,2,3-trichloronaphthalene, 1,2,3,4-tetrachloronaphthalene, 1,2,3,5-tetrachloronaphthalene, 1,2,3, 5,7-pentachloronaphthalene, 1,2,3,4,6-pentachloronaphthalene, 1-bromonaphthalene, 1,2-dibromonaphthalene, 1,3-dibromonaphthalene, 1,4-dibromonaphthalene, 1,5-dibromonaphthalene, 1,6-dibromonaphthalene, 1,7-dibromonaphthalene, 1,8-dibromonaphthalene, 2,3-dibromonaphthalene, 2,4-dibromonaphthalene, 2,5-dibromonaphthalene, 2,6-dibromonaphthalene, 2,7-dibromonaphthalene, 1,4,5-tribromonaphthalene, 1,2,3-tribromonaphthalene, 1,2,3,4-tetrabromonaphthalene, 1,2, 3,5-Tetrabromonaphthalene, 1,2,3,5,7-Pentabromonaphthalene, 1,2,3,4,6-Pentabromonaphthalene, 1-Fluoronaphthalene, 1,2-Difluoronaphthalene, 1,3-Difluoronaphthalene, 1,4-Difluoronaphthalene, 1,5-Difluoronaphthalene, 1,6-Difluoronaphthalene, 1,7-Difluoronaphthalene, 1,8-Difluoronaphthalene, 2,3-Difluoronaphthalene, 2,4-Difluoronaphthalene, 2,5-Difluoronaphthalene, 2,6-Difluoronaphthalene, 2,7-Difluoronaphthalene, 1,4,5-Trifluoronaphthalene, 1,2,3-Trifluoronaphthalene, 1, One or more of 2,3,4-tetrafluoronaphthalene, 1,2,3,5-tetrafluoronaphthalene, 1,2,3,5,7-pentafluoronaphthalene and 1,2,3,4,6-pentafluoronaphthalene; more preferably one or more of 1-chloronaphthalene, 1,2,3,4-tetrachloronaphthalene, 1,2,3,5-tetrachloronaphthalene, 1,2,3,4,6-pentachloronaphthalene, 1-bromonaphthalene, 1-fluoronaphthalene, 1,2,3-trifluoronaphthalene, 1,2,3,4-tetrafluoronaphthalene and 1,2,3,5,7-pentafluoronaphthalene.

[0064] In the present invention, the molecular weight (M n ) is preferably 1000-2000000 g / mol, more preferably 5000-100000 g / mol; the molecular weight distribution is preferably 1-3, more preferably 1.1-1.5; the halogenated content of the photoresist resin material is preferably 5-95%, more preferably 15-60%.

[0065] The present invention also provides a method for preparing the photoresist resin material, comprising the following steps:

[0066] The polymer is dissolved in a solvent, and a halogenating agent is added to carry out a halogenating reaction. After the reaction is completed, the polymer is precipitated to obtain a photoresist resin material.

[0067] In the present invention, the structure of the polymer is:

[0068]

[0069] In the present invention, m and h are the molar ratios of the structural units, preferably, 0<m≤0.9, 0<h≤0.9, m+h=1; more preferably, 0<m≤0.5, 0<h≤0.5.

[0070] In the present invention, R III and R IV Preferably, they are independently one or more of H, -CH3; R1 and Ar in structure (I) are the same as R1 and Ar in structure (II).

[0071] In the present invention, the polymer is one or more of a random copolymer, a block copolymer, and an alternating copolymer; at the same time, the random copolymer, the block copolymer, and the alternating copolymer can also be used as a branch in a branched (or hyperbranched) polymer, a side chain in a comb polymer, and a branch in a star polymer, etc. More preferably, it is a random copolymer.

[0072] In the present invention, the polymer molecular weight (M n ) is preferably 1000-2000000 g / mol, more preferably 5000-100000 g / mol; the molecular weight distribution is preferably 1.0-3, more preferably 1.1-1.5.

[0073] In the present invention, the solvent is preferably carbon tetrachloride, 1,1,2,2-tetrachloroethane, anisole, propylene glycol monoalkyl ether, toluene, chlorobenzene, benzene, chloroform, dichloromethane, hexane, butyl acetate, neopentyl acetate, ethyl lactate, butyl lactate, amyl lactate, propylene glycol alkyl ether acetate, ethyl acetate, butyl acetate, dimethylformamide, cyclopentanone, cyclohexanone, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethyl Preferably, the present invention is one or more of acetamide, N-methylpyrrolidone; more preferably, carbon tetrachloride, 1,1,2,2-tetrachloroethane, anisole, propylene glycol monoalkyl ether, toluene, chlorobenzene, neopentyl acetate, ethyl lactate, propylene glycol alkyl ether acetate, and methyl isobutyl ketone; more preferably, carbon tetrachloride, 1,1,2,2-tetrachloroethane, anisole, propylene glycol monoalkyl ether, propylene glycol alkyl ether acetate, methyl isobutyl ketone, and one or more of neopentyl acetate.

[0074] In the present invention, the halogenating agent is preferably a mixture of N-chlorosuccinimide and benzoyl peroxide, a mixture of N-bromosuccinimide and benzoyl peroxide, a mixture of N-chlorosuccinimide and azobisisobutyronitrile, a mixture of N-bromosuccinimide and azobisisobutyronitrile, a mixture of N-chlorosuccinimide and sodium hydride, a mixture of N-bromosuccinimide and sodium hydride, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and azobisisobutyronitrile, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and benzoyl peroxide, carbon tetrachloride and A mixture of lithium diisopropylamide, a mixture of ClF3, BrF3, PCl3, SO2Cl2, CF3OF, a mixture of Br2, Cl2, F2, HBr and dimethyl sulfoxide, a mixture of HCl and dimethyl sulfoxide, a mixture of HF and dimethyl sulfoxide, a mixture of NH4Br and potassium persulfate complex salt, a mixture of KBr and potassium persulfate complex salt, a mixture of KCl and potassium persulfate complex salt, a mixture of KBr and NaBO3·4H2O, N-chloroamine, S-chlorodimethylsulfonium chloride, S-chlorodimethylsulfonium bromide , a mixture of CuBr2 and tert-butyl nitrite, a mixture of bromine-1,4-dioxane or more; further preferably a mixture of N-chlorosuccinimide and benzoyl peroxide, a mixture of N-bromosuccinimide and benzoyl peroxide, a mixture of N-chlorosuccinimide and azobisisobutyronitrile, a mixture of N-bromosuccinimide and azobisisobutyronitrile, a mixture of N-chlorosuccinimide and sodium hydride, a mixture of N-bromosuccinimide and sodium hydride, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and azobisisobutyronitrile, One or more of a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and benzoyl peroxide, a mixture of carbon tetrachloride and lithium diisopropylamide; more preferably a mixture of N-chlorosuccinimide and benzoyl peroxide, a mixture of N-chlorosuccinimide and azobisisobutyronitrile, a mixture of N-bromosuccinimide and azobisisobutyronitrile, a mixture of N-chlorosuccinimide and sodium hydride, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and azobisisobutyronitrile, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and benzoyl peroxide;

[0075] In the present invention, the reaction temperature of the halogenation reaction is -80 to 90°C, and the reaction time is 0.5 to 96 hours.

[0076] In the present invention, the molar percentage of halogen in the halogen-modified photoresist resin material is preferably 5 to 95%, more preferably 15 to 60%, and even more preferably 20 to 40%.

[0077] The present invention also provides the use of the halogenated modified photoresist resin material in photoresist. The photoresist comprises 1-15% of the halogenated modified photoresist resin material, 0.001-0.1% of an auxiliary agent and 84.9-98.999% of an organic solvent.

[0078] In the present invention, the preparation method of the photoresist is not particularly limited and may include the following steps: adding the halogenated modified photoresist resin material, additives and organic solvent into a light-proof glass container in sequence according to the formula ratio, shaking in the dark for 12 to 96 hours to fully dissolve it; then filtering the photoresist solution with a filter of 0.5 μm or less; collecting the filtrate in a light-proof glass to obtain a photoresist.

[0079] In the present invention, the organic solvent is one or more of anisole, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, methyl isobutyl ketone, cyclopentanone, cyclohexanone, methyl ethyl ketone, diheptanone, ethyl lactate, ethyl acetate, butyl acetate, neopentyl acetate, xylene and toluene. In the present invention, there is no particular restriction on the type and amount of the auxiliary agent, and the auxiliary agent includes leveling agent, defoamer, sensitizer, tackifier, plasticizer, dye, diluent and the like that can optimize the performance of the photoresist. For example, a leveling agent or a defoamer is added to the photoresist, the leveling agent can reduce the surface tension of the photoresist, and the defoamer can reduce the bubbles in the photoresist, so as to promote the uniform distribution of the photoresist layer prepared by the photoresist composition, and prevent the occurrence of spots or scars, etc.

[0080] There is no special restriction on the resolution test method: use a coating machine to coat the wafer with glue, adjust the spin coating speed according to the thickness of the photoresist layer, and after the spin coating is completed, bake the film to form a photoresist layer of a certain thickness; expose it with electron beam radiation or extreme ultraviolet light radiation; then, develop it with a developer and fix it with a fixer; the minimum line width that can be clearly observed after development.

[0081] In the present invention, the baking temperature for hardening the film is preferably 80 to 180° C., more preferably 100 to 120° C.; the baking time is preferably 40 to 240 seconds, more preferably 120 to 180 seconds.

[0082] In the present invention, the developer is preferably one or more of amyl acetate, methyl isobutyl ketone, amyl acetate, isopropyl alcohol mixed solution, methyl isobutyl ketone, and isopropyl alcohol, and is more preferably amyl acetate.

[0083] In the present invention, the development time is preferably 40 to 180 seconds, and more preferably 50 to 60 seconds.

[0084] In the present invention, the fixing solution is isopropyl alcohol, and the fixing time is 30 to 60 seconds, preferably, the fixing time is 40 to 50 seconds.

[0085] In the present invention, the photoresist is coated on the surface of a wafer, pre-baked, exposed, developed and fixed to finally obtain a photolithographic pattern.

[0086] In the present invention, the pre-baking temperature is preferably 80 to 180° C., more preferably 100 to 120° C.; the pre-baking time is preferably 40 to 240 seconds, more preferably 120 to 180 seconds.

[0087] In the present invention, the exposure dose is preferably 1 to 40 μC / cm 2 , more preferably 2 to 25 μC / cm 2 .

[0088] In the present invention, the developer used in the development is preferably amyl acetate, methyl isobutyl ketone, an amyl acetate / isopropyl alcohol mixed solution, or a methyl isobutyl ketone / isopropyl alcohol mixed solution, and more preferably amyl acetate.

[0089] In the present invention, the development time is preferably 40 to 180 seconds, more preferably 50 to 60 seconds.

[0090] In the present invention, the fixing solution used in the fixing is isopropyl alcohol, and the fixing time is preferably 30 to 60 seconds, and more preferably 40 to 50 seconds.

[0091] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0092] Example 1

[0093] 2g polystyrene-r-polymethyl methacrylate (M n =19700), 1.7g N-bromosuccinimide (NBS), 0.37g benzoyl peroxide (BPO) were added to the reaction bottle, and then 38mL carbon tetrachloride was added to dissolve. Nitrogen was blown in the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated polystyrene-r-polymethyl methacrylate (bromine content 23%). The glass transition temperature of brominated polystyrene-r-polymethyl methacrylate increased from 101.5°C to 130.8°C.

[0094] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 50s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0095] Example 2

[0096] 2g polystyrene-r-polymethyl methacrylate (M n =100000), 1.7g N-bromosuccinimide (NBS), 0.37g benzoyl peroxide (BPO) were added to the reaction bottle, and then 40mL carbon tetrachloride was added to dissolve. Nitrogen was blown in the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated polystyrene-r-polymethyl methacrylate (bromine content 20%). The glass transition temperature of brominated polystyrene-r-polymethyl methacrylate increased from 101.5°C to 123.6°C.

[0097] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 60s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0098] Example 3

[0099] 2g polystyrene-r-polymethyl methacrylate (M n =5000), 1.7g N-bromosuccinimide (NBS), 0.37g benzoyl peroxide (BPO) were added to the reaction bottle, and then 40mL carbon tetrachloride was added to dissolve. Nitrogen was blown in the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated polystyrene-r-polymethyl methacrylate (bromine content 25%). The glass transition temperature of brominated polystyrene-r-polymethyl methacrylate increased from 101.5°C to 137.7°C.

[0100] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0101] Example 4

[0102] 2g polystyrene-r-polymethyl acrylate (M n =28100), 1 equivalent of benzyltrimethylammonium chloride and iodine tetrachloride, 0.1 equivalent of azobisisobutyronitrile were added to a dry reaction bottle, dissolved in 40 mL of carbon tetrachloride, heated to 70°C and refluxed for 6 hours. Then, cooled to room temperature, precipitated in ethanol, filtered, repeated four times, vacuum dried to obtain a white solid, brominated polystyrene-r-polymethyl acrylate (bromine content 31%).

[0103] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0104] Example 5

[0105] 2g poly-α-methylstyrene-r-polymethyl acrylate (M n =15700), 1.23g N-bromosuccinimide (NBS), 0.45g benzoyl peroxide (BPO) were added to the reaction bottle, and then 24mL of dichloroethane was added to dissolve. Nitrogen was blown in the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL of ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated poly-α-methylstyrene-r-polymethyl acrylate (bromine content 37%). The glass transition temperature of brominated poly-α-methylstyrene-r-polymethyl acrylate increased from 10°C to 90.5°C.

[0106] 1% brominated poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0107] Example 6

[0108] 2g poly-α-methylstyrene-r-polymethyl acrylate (M n =5500), 1.23g N-bromosuccinimide (NBS), 0.45g benzoyl peroxide (BPO) were added to the reaction bottle, and then 30mL of dichloroethane was added to dissolve. Nitrogen was blown in the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL of ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated poly-α-methylstyrene-r-polymethyl acrylate (bromine content 35%). The glass transition temperature of brominated poly-α-methylstyrene-r-polymethyl acrylate increased from 10°C to 90.4°C.

[0109] 1% brominated poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0110] Example 7

[0111] 2g poly-α-methylstyrene-r-polymethyl acrylate (M n =98500), 1.48g N-bromosuccinimide (NBS), 0.54g benzoyl peroxide (BPO) were added to the reaction bottle, and then 30mL of dichloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 80°C for reaction for 6h. Cooled to room temperature, precipitated in 400mL of ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is brominated poly-α-methylstyrene-r-polymethyl acrylate (bromine content 40%). The glass transition temperature of brominated poly-α-methylstyrene-r-polymethyl acrylate increased from 10°C to 100.1°C.

[0112] 1% brominated poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0113] Example 8

[0114] 2g polymethyl acrylate (M n =15700) was added to a dry reaction bottle, dissolved in 10 mL of dry tetrahydrofuran, and cooled to -78°C. Then 23.2 mmol of lithium diisopropylamide (LDA) and 17.4 mmol of carbon tetrachloride were added and stirred for 24 h. Then the system was warmed to room temperature, precipitated in ethanol, and filtered. This was repeated four times and vacuum dried to obtain a white solid, chloropolymethyl acrylate (chlorine content 65%).

[0115] 1% chloropolymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, the photoresist pattern was developed in methyl isobutyl ketone / isopropanol for 40s and fixed in isopropanol for 60s to obtain the photoresist pattern. The exposure performance is shown in Table 1.

[0116] Example 9

[0117] 2 g of polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n =18800), 2g N-bromosuccinimide (NBS), 116mg benzoyl peroxide (BPO), 68.6mg cuprous bromide were added to the reaction bottle respectively, and then 20mL carbon tetrachloride was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 70°C for reaction for 10h. Cooled to room temperature, 10mL tetrahydrofuran was added to dilute, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, brominated polystyrene-r-polymethyl methacrylate (bromine content 46%).

[0118] Add 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 into a light-proof glass bottle. Shake at room temperature for 12 hours to fully dissolve the mixture. Filter the mixture solution with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system is used for exposure verification. After the exposure, develop in methyl isobutyl ketone and isopropanol for 50s, and fix in isopropanol for 60s to obtain a photoresist pattern. SEM morphology is as follows: Figure 1 The exposure performance is shown in Table 1.

[0119] Depend on Figure 1 It can be seen that the photoresist resin obtained by the present invention has excellent exposure performance, and the aspect ratio of the pattern after development is 5:1.

[0120] Example 10

[0121] 2 g of polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n =5300), 2g N-bromosuccinimide (NBS), 116mg benzoyl peroxide (BPO), 68.6mg cuprous bromide were added to the reaction bottle respectively, and then 20mL carbon tetrachloride was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 70°C for reaction for 10h. Cooled to room temperature, 10mL tetrahydrofuran was added to dilute, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, brominated polystyrene-r-polymethyl methacrylate (bromine content 50%).

[0122] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 60s and fixed in isopropanol for 60s to obtain a photoresist pattern. The exposure performance is shown in Table 1.

[0123] Embodiment 11

[0124] 5 g polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n=44700), 2g N-chlorosuccinimide (NCS), 188mg benzoyl peroxide (BPO), 85.7mg cuprous bromide were added to the reaction bottle, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was vacuum dried, which was chloropolystyrene-r-polymethyl methacrylate (chlorine content 27%). The glass transition temperature of chloropolystyrene-r-polymethyl methacrylate increased from 110.8℃ to 149.5℃.

[0125] 1% chloropolystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 50s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0126] Example 12

[0127] 5 g polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n =5500), 2g N-chlorosuccinimide (NCS), 188mg benzoyl peroxide (BPO), 85.7mg cuprous bromide were added to the reaction bottle, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was vacuum dried, which was chloropolystyrene-r-polymethyl methacrylate (chlorine content 30%). The glass transition temperature of chloropolystyrene-r-polymethyl methacrylate increased from 110.8℃ to 149.8℃.

[0128] 1% chloropolystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 50s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0129] Embodiment 13

[0130] 5 g polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n =1050000), 2g N-chlorosuccinimide (NCS), 188mg benzoyl peroxide (BPO), 85.7mg cuprous bromide were added to the reaction bottle respectively, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was vacuum dried, which was chloropolystyrene-r-polymethyl methacrylate (chlorine content 30%). The glass transition temperature of chloropolystyrene-r-polymethyl methacrylate increased from 110.8℃ to 149.5℃.

[0131] 1% chloropolystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 50s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0132] The photoresist prepared in this example was exposed at the EUV line station of Shanghai Light Source for verification, with an exposure dose of 60 mJ / cm 2 After the exposure, the film was developed in amyl acetate for 30 seconds and fixed in isopropyl alcohol for 60 seconds to obtain a photoresist pattern with a period of 75 nm. The aspect ratio of the developed pattern was 4:1.

[0133] Embodiment 14

[0134] 2 g polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =80100) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 23.2mmol lithium diisopropylamide (LDA) and 17.4mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 23%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 133.2°C.

[0135] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0136] Embodiment 15

[0137] 2 g polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =5100) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 23.2mmol lithium diisopropylamide (LDA) and 17.4mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 30%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 139.2°C.

[0138] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0139] The photoresist prepared in this example was exposed at the EUV line station of Shanghai Light Source for verification, with an exposure dose of 40 mJ / cm 2 After the exposure, the film was developed in amyl acetate for 30 seconds and fixed in isopropyl alcohol for 60 seconds to obtain a photoresist pattern with a period of 55 and an aspect ratio of 4:1 after development.

[0140] Example 16

[0141] 2 g of polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n=49000) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 23.2mmol lithium diisopropylamide (LDA) and 17.4mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 30%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 139.6°C.

[0142] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0143] The photoresist prepared in this example was exposed at the EUV line station of Shanghai Light Source for verification, with an exposure dose of 60 mJ / cm 2 After the exposure, the film was developed in amyl acetate for 30 seconds and fixed in isopropyl alcohol for 60 seconds to obtain a photoresist pattern with a period of 70 nm. The aspect ratio of the developed pattern was 4:1.

[0144] Embodiment 17

[0145] 2 g polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =18000) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 23.2mmol lithium diisopropylamide (LDA) and 17.4mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 30%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 139.6°C.

[0146] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 40s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0147] Embodiment 18

[0148] 2 g of polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =18000) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 11.6mmol lithium diisopropylamide (LDA) and 8.7mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 10%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 125.3°C.

[0149] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s to obtain a photoresist pattern with a period of 40nm. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0150] Embodiment 19

[0151] 2 g of polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =18000) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 46.4mmol lithium diisopropylamide (LDA) and 34.8mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 56%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 140.2°C.

[0152] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0153] Embodiment 20

[0154] 2 g polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =81300) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 38.3mmol lithium diisopropylamide (LDA) and 28.7mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 46%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 151.8°C.

[0155] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 40s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0156] Embodiment 21

[0157] 2g polyphenylvinyl ketone (PPhVK, M n =95100), 1 equivalent of thionyl chloride was added to a dry reaction bottle, dissolved in 40 mL of chloroform, heated to 50°C and refluxed for 1.5 h. Then, cooled to room temperature, precipitated in methanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is chloropolyphenylpropenyl ketone (chlorine content 36%). The glass transition temperature of chloropolyphenylpropenyl ketone increased from 76.8°C to 170.1°C.

[0158] Add 2% chloropolyphenyl propylene ketone and 98% anisole to a light-proof glass bottle. Shake at room temperature for 12 hours to fully dissolve the mixture. Filter the mixture solution with 0.5μm, 0.2μm and 0.02μm filters in turn. Finally, the electron beam exposure system is used for exposure verification. After the exposure, it is developed in methyl isobutyl ketone and isopropanol for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern is 3:1. The exposure performance is shown in Table 1.

[0159] Embodiment 22

[0160] 2g polyphenylvinyl ketone (PPhVK, M n =248800), 2 times equivalent of thionyl chloride was added to a dry reaction bottle, dissolved in 40 mL of chloroform, heated to 50°C and refluxed for 1.5 h. Then, cooled to room temperature, precipitated in methanol, filtered, repeated four times, vacuum dried to obtain a white solid, which is chloropolyphenyl propenyl ketone (chlorine content 64%). The glass transition temperature of chloropolyphenyl propenyl ketone increased from 76.8°C to 180.6°C.

[0161] 1% chloropolyphenyl propylene ketone, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, the photoresist pattern was developed in methyl isobutyl ketone and isopropanol for 40s and fixed in isopropanol for 60s to obtain the photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0162] Embodiment 23

[0163] 2 g poly 1-pentene-3-one (PEVK, M n =67400), 1 equivalent of thionyl chloride was added to a dry reaction bottle, dissolved in 60 mL of carbon tetrachloride, heated to 50°C and refluxed for 2 hours. Then, cooled to room temperature, precipitated in methanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is chloropoly-1-pentene-3-one (chlorine content 16%). The glass transition temperature of chloropoly-1-pentene-3-one increased from 25.0°C to 75.2°C.

[0164] 1% chloropoly-1-pentene-3-one, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, the photoresist pattern was developed in methyl isobutyl ketone for 40s and fixed in isopropanol for 60s to obtain the photoresist pattern. The aspect ratio of the developed pattern was 2:1. The exposure performance is shown in Table 1.

[0165] Embodiment 24

[0166] 2 g poly 1-pentene-3-one (PEVK, M n =67400), 3.5 times equivalent of thionyl chloride was added to a dry reaction bottle, dissolved in 120 mL of carbon tetrachloride, heated to 50°C and refluxed for 2 hours. Then, cooled to room temperature, precipitated in methanol, filtered, repeated four times, vacuum dried to obtain a white solid, which is chloropoly-1-pentene-3-one (chlorine content 42%). The glass transition temperature of chloropoly-1-pentene-3-one increased from 25.0°C to 108.8°C.

[0167] 1% chloropoly-1-pentene-3-one, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, the photoresist pattern was developed in methyl isobutyl ketone for 40s and fixed in isopropanol for 50s to obtain the photoresist pattern. The aspect ratio of the developed pattern was 2:1. The exposure performance is shown in Table 1.

[0168] Embodiment 25

[0169] 2g polyphenylvinyl ketone (PPhVK, M n =95100), 1 equivalent of thionyl chloride was added to a dry reaction bottle, dissolved in 40 mL of chloroform, heated to 50°C and refluxed for 20 min. Then, cooled to room temperature, precipitated in methanol, filtered, repeated four times, and vacuum dried to obtain a white solid, which is chloropolyphenyl propenyl ketone (chlorine content 12%). The glass transition temperature of chloropolyphenyl propenyl ketone increased from 76.8°C to 108.9°C.

[0170] 2% chloropolyphenyl propylene ketone and 98% anisole were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, the photoresist pattern was developed in methyl isobutyl ketone and isopropanol for 40s and fixed in isopropanol for 60s to obtain the photoresist pattern. The aspect ratio of the developed pattern was 3:1. The exposure performance is shown in Table 1.

[0171] Embodiment 26

[0172] 2 g of polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =44700) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 30mmol lithium diisopropylamide (LDA) and 22.5mmol carbon tetrachloride were added and stirred for 24h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 38%). That is, the glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 150.2°C.

[0173] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 40s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0174] Embodiment 27

[0175] 2 g poly-α-methylstyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =68700), 2g N-chlorosuccinimide (NCS), 180mg benzoyl peroxide (BPO), 85mg cuprous bromide were added to the reaction bottle, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was dried under vacuum, which was chlorinated poly-α-methylstyrene-r-polymethyl acrylate (chlorine content 50%).

[0176] 1% chloro-poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0177] Embodiment 28

[0178] 3 g poly-α-methylstyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =68700), 2g N-chlorosuccinimide (NCS), 180mg benzoyl peroxide (BPO), 85mg cuprous bromide were added to the reaction bottle, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was dried in vacuum to obtain chlorinated poly-α-methylstyrene-r-polymethyl acrylate (chlorine content 36%).

[0179] 1% chloro-poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 40s and fixed in isopropanol for 60s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0180] Embodiment 29

[0181] 4 g poly-α-methylstyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n =68700), 2g N-chlorosuccinimide (NCS), 180mg benzoyl peroxide (BPO), 85mg cuprous bromide were added to the reaction bottle, and then 50mL of 1,1,2,2-tetrachloroethane was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 60℃ for reaction for 24h. Cool to room temperature, precipitate in methanol, and filter. The filter cake was dissolved in tetrahydrofuran, precipitated in methanol, filtered, and repeated four times. The white solid was dried under vacuum, which was chlorinated poly-α-methylstyrene-r-polymethyl acrylate (chlorine content 25%).

[0182] 1% chloro-poly-α-methylstyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 40s and fixed in isopropanol for 50s to obtain a photoresist pattern. The aspect ratio of the developed pattern was 5:1. The exposure performance is shown in Table 1.

[0183] Comparative Example 1

[0184] 2 g of polystyrene-r-polymethyl methacrylate random copolymer (PS-r-PMMA, M n =950300), 4g N-bromosuccinimide (NBS), 232mg benzoyl peroxide (BPO), 137.2mg cuprous bromide were added to the reaction bottle respectively, and then 20mL carbon tetrachloride was added to dissolve. Nitrogen was blown into the reaction bottle for 30min and placed in an oil bath at 70°C for reaction for 10h. Cooled to room temperature, 10mL tetrahydrofuran was added to dilute, precipitated in 400mL ethanol, filtered, repeated four times, and vacuum dried to obtain a white solid, brominated polystyrene-r-polymethyl methacrylate (bromine content 80%).

[0185] 1% brominated polystyrene-r-polymethyl methacrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in methyl isobutyl ketone / isopropanol for 50s and fixed in isopropanol for 60s. The roughness of the line edge of the obtained photoresist pattern was too large, and the graphic quality was poor and there were many defects. The exposure performance is shown in Table 1.

[0186] Comparative Example 2

[0187] 2 g polystyrene-r-polymethyl acrylate random copolymer (PS-r-PMA, M n=18000) was added to a dry reaction bottle, dissolved in 10mL dry tetrahydrofuran, and cooled to -78°C. Then 58.0mmol lithium diisopropylamide (LDA) and 43.5mmol carbon tetrachloride were added and stirred for 12h. Then the system was warmed to room temperature, precipitated in ethanol, filtered, and repeated four times. A white solid was obtained by vacuum drying, which was chloropolystyrene-r-polymethyl acrylate (chlorine content 86%). The glass transition temperature of chloropolystyrene-r-polymethyl acrylate increased from 110.8°C to 142.5°C.

[0188] 1% chloropolystyrene-r-polymethyl acrylate, 98.999% anisole, and 0.001% leveling agent IOTA3000 were added to a light-proof glass bottle. At room temperature, shake for 12 hours to fully dissolve the mixture. The mixture solution was filtered with 0.5μm, 0.2μm, and 0.02μm filters in turn. Finally, the electron beam exposure system was used for exposure verification. After the exposure, it was developed in amyl acetate for 30s and fixed in isopropanol for 50s. The obtained photoresist pattern had poor quality, the lines collapsed, and there was adhesion between the lines. The exposure performance is shown in Table 1.

[0189] The exposure performance of the photoresist resin material obtained by the present invention and commercial photoresist products were tested under the same conditions, and the results are shown in Table 1 below.

[0190] Table 1 Exposure performance of the photoresist resin material obtained by the present invention and commercial photoresist products

[0191]

[0192]

[0193] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A halogenated modified photoresist resin material, characterized in that: The structure of the photoresist resin material is: Wherein, u, v and w are the molar proportions of the structural unit, 0≤u<0.8, 0<v≤0.9, 0<w≤0.9, u+v+w=1; R' is one or more of H, -CH3 and X; X is one or more of -Cl, -Br, and -F; R″ is one or more of H, -CH3 and Y, wherein Y is one or more of -Cl, -Br, -F; Ar is one or more of a benzene ring and its derivatives, a naphthalene ring and its derivatives; n is a positive integer; R1 is one or more of Formula I and Formula II; Wherein, R2 and R3 are independently -H, -CH3, -CH2CH3, C3~C 12 One or more of alkanes, benzene rings and their derivatives, naphthalene rings and their derivatives; The benzene ring and its derivatives and the naphthalene ring and its derivatives are independently one or more of benzene, phenol, toluene, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, benzyl alcohol, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, dimethylnaphthalene, methylnaphthalene, trimethylnaphthalene, and naphthalenemethanol; The halogenated mole percentage of the halogenated modified photoresist resin material is 5-65%.

2. The halogenated modified photoresist resin material according to claim 1, characterized in that: The u, v and w are the molar ratios of the structural unit, 0≤u<0.2, 0<v≤0.7, 0<w≤0.8, u+v+w=1.

3. The halogen-modified photoresist resin material according to claim 1, characterized in that: The n is a positive integer of 1≤n≤5.

4. The method for preparing the halogenated modified photoresist resin material according to any one of claims 1 to 3, characterized in that: The steps include: The polymer is dissolved in a solvent, and a halogenating agent is added to carry out a halogenating reaction. After the reaction is completed, the polymer is precipitated to obtain a halogenated modified photoresist resin material.

5. The method for preparing the halogenated modified photoresist resin material according to claim 4, characterized in that: The structure of the polymer is: Wherein, m and h are the molar proportions of the structural unit, 0<m≤0.9, 0<h≤0.9, m+h=1; R III and R IV are independently one or more of H, -CH3; Ar is one or more of a benzene ring and its derivatives, a naphthalene ring and its derivatives; R1 is one or more of Formula I and Formula II; Wherein, R2 and R3 are independently -H, -CH3, -CH2CH3, C3~C 12 One or more of alkanes, benzene rings and their derivatives, naphthalene rings and their derivatives.

6. The method for preparing the halogenated modified photoresist resin material according to claim 5, characterized in that: The benzene ring and its derivatives and the naphthalene ring and its derivatives are independently one or more of benzene, phenol, toluene, xylene, ethylbenzene, trimethylbenzene, halogenated benzene, benzyl alcohol, naphthalene, halogenated naphthalene, naphthol, nitronaphthalene, dimethylnaphthalene, methylnaphthalene, trimethylnaphthalene and naphthalenemethanol.

7. The method for preparing the halogenated modified photoresist resin material according to claim 5 or 6, characterized in that: The polymer is one or more of a random copolymer, a block copolymer, and an alternating copolymer; the solvent is one or more of carbon tetrachloride, 1,1,2,2-tetrachloroethane, anisole, propylene glycol monoalkyl ether, toluene, chlorobenzene, benzene, chloroform, dichloromethane, hexane, butyl acetate, neopentyl acetate, ethyl lactate, butyl lactate, amyl lactate, propylene glycol alkyl ether acetate, ethyl acetate, butyl acetate, cyclopentanone, cyclohexanone, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

8. The method for preparing the halogen-modified photoresist resin material according to claim 7, characterized in that: The halogenating agent is a mixture of N-chlorosuccinimide and benzoyl peroxide, a mixture of N-bromosuccinimide and benzoyl peroxide, a mixture of N-chlorosuccinimide and azobisisobutyronitrile, a mixture of N-bromosuccinimide and azobisisobutyronitrile, a mixture of N-chlorosuccinimide and sodium hydride, a mixture of N-bromosuccinimide and sodium hydride, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and azobisisobutyronitrile, a mixture of iodine tetrachloride, benzyltrimethylammonium chloride and benzoyl peroxide, a mixture of carbon tetrachloride and lithium diisopropylamide, ClF3, BrF3, PC l3, SO2Cl2, CF3OF, Br2, Cl2, F2, a mixture of HBr and dimethyl sulfoxide, a mixture of HCl and dimethyl sulfoxide, a mixture of HF and dimethyl sulfoxide, a mixture of NH4Br and potassium persulfate complex salt, a mixture of KBr and potassium persulfate complex salt, a mixture of KCl and potassium persulfate complex salt, a mixture of KBr and NaBO3·4H2O, one or more of N-chloroamine, S-chlorodimethylsulfonium chloride, S-chlorodimethylsulfonium bromide, a mixture of CuBr2 and tert-butyl nitrite, and a mixture of bromo-1,4-dioxane.

9. The method for preparing the halogenated modified photoresist resin material according to claim 4, characterized in that: The reaction temperature of the halogenation reaction is -80 to 90° C., and the reaction time is 0.5 to 96 hours.

10. Use of the halogenated modified photoresist resin material according to any one of claims 1 to 3 in photoresist.

Citation Information

Patent Citations

  • Polymer resin and preparation method thereof, method for overcoming cracking of electron beam photoresist, electron beam photoresist as well as preparation and application of electron beam photoresist

    CN113773433A

  • Polymer resin for electron beam photoresist and preparation method thereof

    CN114957532A